2019
DOI: 10.1021/acs.jpcc.9b04607
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of Heteroatom Substitution on Nitrogen and Phosphorus Co-Doped Graphene as a High Active Catalyst for Hydrogen Evolution Reaction

Abstract: Graphene doped with heteroatoms is known to create a unique electronic structure with comparatively much higher active sites by the synergistic coupling effect. However, in the earlier attempts, the atomic structure of such co-doped graphene could not be altered; thus, there is a lack of reports discussing the influence of the atomic arrangement in the catalytic performance of the co-doped graphene. Here, by co-doping P and N atoms in graphene as a model system, we present a facile and two-step process wherein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 71 publications
3
38
0
Order By: Relevance
“…To activate pristine carbon materials, heteroatoms such as N, S, O, and P have to be doped into carbon matrix to induce charge polarization of carbon atoms, alter the electronic structure and local density of states, or introduce structural defects, which may possibly bring about distinct catalytic properties. [199][200][201][202] Heteroatom doped carbon materials have been widely used for efficiently catalyzing hydrogen evolution reaction, oxygen reduction reaction, electrochemical CO 2 reduction, oxygen evolution reaction, etc. [22,81,116,200,201] Regarding OER in acidic electrolytes, carbon based electrocatalysts including heteroatom doped carbon and hybrid carbon materials have been developed to boost the reaction kinetics.…”
Section: Carbon-based Nanomaterialsmentioning
confidence: 99%
“…To activate pristine carbon materials, heteroatoms such as N, S, O, and P have to be doped into carbon matrix to induce charge polarization of carbon atoms, alter the electronic structure and local density of states, or introduce structural defects, which may possibly bring about distinct catalytic properties. [199][200][201][202] Heteroatom doped carbon materials have been widely used for efficiently catalyzing hydrogen evolution reaction, oxygen reduction reaction, electrochemical CO 2 reduction, oxygen evolution reaction, etc. [22,81,116,200,201] Regarding OER in acidic electrolytes, carbon based electrocatalysts including heteroatom doped carbon and hybrid carbon materials have been developed to boost the reaction kinetics.…”
Section: Carbon-based Nanomaterialsmentioning
confidence: 99%
“…Along with the monodoped carbon catalysts discussed above, co‐doping of carbon materials with two or more different heteroatoms can further enhance the catalytic performance of the carbon catalysts by increasing the total number of active sites and through possible synergistic effects. [ 47 ] So far, co‐doping studies have been focused on co‐doping of N‐doped carbon materials with a second element, such as B, [ 69–76 ] S, [ 77–88 ] P, [ 89–106 ] and, to a less extent, Cl, [ 107 ] and Si. [ 108,109 ] A few reports on the co‐doping of carbon materials with three elements, such as N–P–S, [ 110,111 ] N–P–B, [ 112,113 ] N–P–F, [ 114 ] and N–S–F, [ 115 ] have recently appeared.…”
Section: Co‐doped C‐mfecsmentioning
confidence: 99%
“…Current reports indicate that the sequence of doping helps in manipulating the heteroatom substitution, leading to a dramatic influence on the electrocatalytic properties. [ 95 ] Hung et al. found that the P doped graphene followed by the N‐doping is of great importance in defining a better crystallinity and conductivity and favorable elemental functionalities than the corresponding materials from the inverse doping sequencing.…”
Section: Co‐doped C‐mfecsmentioning
confidence: 99%
“…Heteroatomic doping of CQD not only improves fluorescence efficiency but also provides active sites in CQD to expand its potential applications in analysis and sensing [ 24 ]. Through the synergistic coupling effect, heteroatom-doped carbon materials can produce unique electronic structures with higher active sites [ 49 , 50 ]. In particular, nitrogen doping plays an important role in the regulation of electronic and chemical properties of carbon materials.…”
Section: Introductionmentioning
confidence: 99%